2005
DOI: 10.1111/j.1526-4637.2005.05003.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Occupational Low Back Injuries: Predicting Pain-Related Disability from Satisfaction with Case Management in African Americans and Caucasians

Abstract: For African Americans and lower socioeconomic status persons in the Workers' Compensation system, less treatment/compensation was associated with lower satisfaction with the process, which in turn predicted higher levels of post-settlement disability. Given that the function of Workers' Compensation is to reduce disability from work-related injuries, the current results suggest that the system produces inequitable outcomes for these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…The race finding is consistent with previous analyses of the DOLOR cohort, in which blacks, relative to whites, received lower ratings of residual disability at case settlement, were less likely to have a specific diagnosis or surgery, were less satisfied with their WC experience, and had poorer long-term outcomes with respect to pain, function, and psychologic state. [1][2][3][4] The satisfaction effects are consistent with other research that has documented increases in disability as a function of negative postinjury experiences with employers, healthcare providers, and case managers. 23,24,[37][38][39][40][41] Explanations for the race and satisfaction findings must of necessity be speculative.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The race finding is consistent with previous analyses of the DOLOR cohort, in which blacks, relative to whites, received lower ratings of residual disability at case settlement, were less likely to have a specific diagnosis or surgery, were less satisfied with their WC experience, and had poorer long-term outcomes with respect to pain, function, and psychologic state. [1][2][3][4] The satisfaction effects are consistent with other research that has documented increases in disability as a function of negative postinjury experiences with employers, healthcare providers, and case managers. 23,24,[37][38][39][40][41] Explanations for the race and satisfaction findings must of necessity be speculative.…”
Section: Discussionsupporting
confidence: 89%
“…4 Full details on the study methodology are provided elsewhere [2][3][4] and are only summarized here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies, 4,5,8,13,34,40,41 we found that African-American participants, on average, reported more pain, interference, and disability than their Caucasian counterparts. In addition, we found that African-American participants reported using diverting attention and prayer and hoping more than Caucasian participants.…”
Section: Discussionsupporting
confidence: 63%
“…[4][5][6]12,30,32 In addition, there are race differences in clinical and experimental pain with African-Americans reporting more clinical pain, lower pain thresholds for ischemic and cold pressor pain, higher pain-related disability, and higher pain unpleasantness than Caucasians. 4,5,8,12,13,33,34,40,41 Other research groups have not found race differences in pain severity. 9,21 Although such research may enhance treatment and prevention with diverse groups, it is essential to also examine variables that might moderate racial group differences in the pain experience.…”
mentioning
confidence: 99%